2016
DOI: 10.1111/jcmm.12772
|View full text |Cite
|
Sign up to set email alerts
|

PAC1R agonist maxadilan enhances hADSC viability and neural differentiation potential

Abstract: Pituitary adenylate cyclase‐activating polypeptide (PACAP) is a structurally endogenous peptide with many biological roles. However, little is known about its presence or effects in human adipose‐derived stem cells (hADSCs). In this study, the expression of PACAP type I receptor (PAC1R) was first confirmed in hADSCs. Maxadilan, a specific agonist of PAC1R, could increase hADSC proliferation as determined by Cell Counting Kit‐8 and cell cycle analysis and promote migration as shown in wound‐healing assays. Maxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Furthermore, those proteins could also be up‐regulated by LiCl (20 mmol/L) added into DMEM‐LG, which is a widely used in the activation of Wnt/β‐catenin signalling . However, those proteins were again down‐regulated in iPS‐CM by XAV939 (XAV, 10 μmol/L) (Figure D,E), an inhibitor of the Wnt/β‐catenin signalling pathway . These results indicated that iPS‐CM might be mainly relied on inherent bFGF to promote the proliferation of ILCs through Wnt/β‐catenin signalling pathway.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, those proteins could also be up‐regulated by LiCl (20 mmol/L) added into DMEM‐LG, which is a widely used in the activation of Wnt/β‐catenin signalling . However, those proteins were again down‐regulated in iPS‐CM by XAV939 (XAV, 10 μmol/L) (Figure D,E), an inhibitor of the Wnt/β‐catenin signalling pathway . These results indicated that iPS‐CM might be mainly relied on inherent bFGF to promote the proliferation of ILCs through Wnt/β‐catenin signalling pathway.…”
Section: Resultsmentioning
confidence: 97%
“…39,40 However, those proteins were again down-regulated in iPS-CM by XAV939 (XAV, 10 lmol/L) ( Figure 6D,E), an inhibitor of the Wnt/b-catenin signalling pathway. 41 These results indicated that iPS-CM might be mainly relied on inherent bFGF to promote the proliferation of ILCs through Wnt/ b-catenin signalling pathway. And the diagram of the mechanisms underlying the promotion anti-apoptosis and proliferation of ILCs by iPS-CM is shown in Figure 6F.…”
Section: Effects Of Ips-cm On Medium Testosterone (T) Levels and Stmentioning
confidence: 87%
“…Lack of PACAP also influences behavior of these animals (Farkas et al 2017), and results in alterations of neuronal development (Rivnyak et al 2018). Not only the absence of the neuropeptide but its addition also affects the differentiation of chondrocytes (Juhasz et al 2014a), neurons (Guo et al 2016), and mammary epithelial cells (Csanaky et al 2014). We have demonstrated earlier that PACAP increases Ca 2+ release in osteoblasts and induces their differentiation (Juhasz et al 2014b).…”
Section: Discussionmentioning
confidence: 92%
“… 49 ANKRD30BP2 , which encoded ankyrin repeat domain 30B pseudogene 2 or CTSP-1, was expressed in 58% of prostate tumors and was capable of eliciting a humoral immune response in about 20% of patients with prostate cancer. 50 The strong expression of CYP2S1 , a cytochromes P450 family member, was associated with poor prognosis of colorectal cancer. 51 Moreover, SH3PXD2A-AS1-correlated lncRNAs, including lnc-RP11-204N11.1.1-3:9, DLX2-AS1, and lnc00458, were also significantly dysregulated (Supplemental Table 1) in the microarray analysis.…”
Section: Discussionmentioning
confidence: 99%